Effectiveness of community based safe motherhood promoters in improving the utilization of obstetric care: the case of Mtwara rural District in Tanzania - Mushi, Declare L.; Mpembeni, Rose; Jahn, Albrecht (BMC pregnancy and childbirth, 2010)
In Tanzania, maternal mortality ratio remains unacceptably high at 578/100,000 live births. Despite a high coverage of antenatal care (96%), only 44% of deliveries take place within the formal health services. Still, "Ensure skilled attendant at birth" is acknowledged as one of the most effective interventions to reduce maternal deaths. Exploring the potential of community-based interventions in increasing the utilization of obstetric care, the study aimed at developing, testing and assessing a community-based safe motherhood intervention in Mtwara rural District of Tanzania.
Gesehen am 17.05.2023